Open Science Practices for Software Engineering Controlled Experiments and Quasi-Experiments - Cordeiro, André F. R.; OliveiraJr, Edson (Anais do Workshop de Práticas de Ciência Aberta para Engenharia de Software (OpenScienSE); 2021: Anais do I Workshop de Práticas de Ciência Aberta para Engenharia de SoftwareDO - 10.5753/opensciense.2021.17140, 2021)
In this vision paper, we present how Open Science practices can be adopted to prospectively support promoting software engineering controlled experiments and quasi-experiments. As experimentation in software engineering has gained extraordinary attention and increased in the last decade, we as com- munity should focus on the openness of experiment artifacts and processes to every citizen, especially those artifacts produced with public and government funding. Such openness might bring several benefits towards evolving this area based on well-reported experiments, artifacts, processes, shared data, and experiences gathered up. In view of this, we envision an open science framework for software engineering controlled experiments and quasi-experiments. In addition, we provide a research agenda, which is intended to be accomplished in the next five years.